Assimilation educational program for Rohingya Children for their survival and development / Shimaa Shazana Mohd Ali ... [et al.] - Mohd Ali, Shimaa Shazana; Ahmad, Yarina; Tahir, Nor Suziwana; Ayob, Nor Azira (2021)
This paper presents an assimilation educational program for Rohingya children for their survival and development in Malaysia. Children deserve protection from authority as they are vulnerable to various issues and circumstances. The right to education, which is the central mechanism of human capital, is one of the most essential aspects in shaping children's behaviour and personality. Education provides knowledge that may prevent the involvement of children in crimes. Hence, education for every child must be prioritised regardless of their status. This product aims to help Rohingya children to assimilate with Malaysian culture and identity that will indirectly help their survival and development in this country. This initiative will employ four strategies, which are the interactive book, selected videos, and stories related to Malaysia, and to be conducted within a week through a quasi-experiment technique. In terms of contribution and novelty, this product can be considered novel because the product (1) serves the international agenda, particularly the Child Rights Convention (CRC) and Sustainable Development Goals (SDGs), (2) utilises "education" as a bridging mechanism to enhance assimilation among Rohingya children in Malaysia, and is (3) comprehensive as it employs proactive strategies in producing the product.